Cognitive Function of Older Adults Relocated for Poverty Alleviation and Its Influencing Factors - YANG Le, LI Zhenhao, YAO Dianrui, YANG Yang, SUN Yufang, HE Ying (Zhongguo quanke yixue, 2025)
Background The cognitive function of older people relocated for poverty alleviation varies. It is of great significance to focus on the cognitive function of older adults relocated for poverty alleviation and identify the influencing factors, thus improving their cognitive function. Objective To illustrate the cognitive function of older adults relocated for poverty alleviation in Shanxi Province, and to identify the influencing factors, thus providing a scientific basis for developing targeted intervention strategies. Methods A multi-stage stratified sampling method was used to survey the relocated older people in 24 resettlement sites of 8 counties in Taiyuan, Xinzhou, Lyuliang and Linfen of Shanxi Province from June to August 2023. A total of 1 882 questionnaires were collected. The cognitive function of the relocated older adults was assessed using the Chinese version of the Mini-mental State Examination (CMMSE). Based on the education level, older adults with primary school or below and CMMSE above 22 points, and those with secondary school/technical secondary school or above and CMMSE above 26 points were considered without cognitive impairment. The hierarchical linear regression model and multivariate Logistic regression analysis model were used to analyze the influencing factors of cognitive impairment from four dimensions, including social demographic characteristics, health-related behaviors, health status, and society and environment. Results A total of 1 848 older adults relocated for poverty alleviation in Shanxi Province were recruited, with the CMMSE score of (24.40±5.84) points. Hierarchical linear regression indicated that age (B=-2.355), education level (primary school and below: B=-2.189), marital status (B=-0.987), physical exercise (B=-0.792), body mass index (BMI, overweight: B=1.034), activity of daily living (ADL, B=0.900), depression (B=-0.089), and social capital (B=0.125) were influencing factors of cognitive function of relocated older adults of Shanxi Province (P<0.05). There were 428 (23.2%) relocated older adults with cognitive impairment. Multivariate Logistic regression showed that age (OR=1.894, 95%CI=1.398-2.566), individual monthly income (≤500 yuan: OR=0.598, 95%CI=0.380-0.943), marital status (OR=1.507, 95%CI=1.078-2.106), physical exercise (OR=1.673, 95%CI=1.276-2.193), BMI (overweight: OR=0.543, 95%CI=0.368-0.804), ADL (OR=0.805, 95%CI=0.823-0.895), and social capital (OR=0.958, 95%CI=0.934-0.983) were influencing factors of cognitive impairment of relocated older adults of Shanxi Province (P<0.05) . Conclusion The detection rate of cognitive impairment in older adults relocated for poverty alleviation in Shanxi Province is 23.2%. Age, education level, marital status, physical exercise, ADL, depression, BMI and social capital are important factors affecting the cognitive function of the relocated older adults in Shanxi Province. More effective interventions targeted at these factors should be taken to prevent cognitive decline among them.